The formulation of classification for islamization in medicine: Review on 15 years of publications from Kulliyyah of Medicine - Shahar M.A.; Idris M.F.; Mohamad C.A.C.; Razali Z.A. (International Islamic University Malaysia, 2024)
The Kulliyyah of Medicine of IIUM has pioneered the Islamization of Medicine in Malaysia since its establishment in year 1994. Therefore, it is timely to review publications on Islamization by the kulliyyah and also to propose a classification system in the field of researches to promote an organized, comprehensive, inclusive and relevant Islamization process. The aim is to review and classify publications on Islamization performed by the members of Kulliyyah of Medicine, International Islamic University Malaysia (IIUM). All researches and publications deposited in the IIUM Repository (IREP) under the Kulliyyah of Medicine between 1 st of January 2000 and 31 st of August 2016 were reviewed. Journal articles, posters and proceedings with Islamization themes were identified. These publications were classified based on common themes to either of the following; 1) "Islamic Principles and Related Rulings in Medicine"; 2) "Medical Treatment for Muslim Patients"; 3) "Islamic Input in Medical Practices"; 4) "Ruqyah and Tibb an-Nabawi in Contemporary Medicine". A total of 1616 items (journal articles, abstracts and proceedings) were reviewed. Sixty-one (3.8%) of them were related to Islamization. The major contributors to writings in Islamization are the Orthopaedics, Traumatology and Rehabilitation Department (10%) followed by the Internal Medicine Department (7.9%), from their total deposits in the IREP database. Majority (36.5%) of work were done in "Islamic Principles and Related Rulings in Medicine", which dwells in subjects such as euthanasia, autonomy and doctor-patient relationship followed by "Islamic Input in Medical Practice" (28.6%) which was related to topics in the medical curriculum such as Fiqh Ibadah for the sick. Twenty-three point eight percent (23.8%) of work were in the "Medical Treatment for Muslim Patients" which focuses on Ramadan and diabetes and joint problems and Solat. Minimal work (7.9%) was done in the "Ruqyah and Tibb an-Nabawi in Contemporary Medicine" category. Low number of publications on Islamization was deposited in the IREP database for the past 15 years. Based on the proposed classification system, majority of publications were on "Islamic Principles and Related Rulings in Medicine" and "Islamic Input in Medical Practice". More work is required on the theme of "Medical Treatment for Muslim Patients" and "Ruqyah and Tibb an-Nabawi in Contemporary Medicine". 2019 Default.